2022
DOI: 10.1002/anie.202214487
|View full text |Cite
|
Sign up to set email alerts
|

Interparticle Charge‐Transport‐Enhanced Electrochemiluminescence of Quantum‐Dot Aerogels

Abstract: Electrochemiluminescence (ECL) represents a widely explored technique to generate light, in which the emission intensity relies critically on the charge‐transfer reactions between electrogenerated radicals. Two types of charge‐transfer mechanisms have been postulated for ECL generation, but the manipulation and effective probing of these routes remain a fundamental challenge. Here, we demonstrate the design of quantum dot (QD) aerogels as novel ECL luminophores via a versatile water‐induced gelation strategy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…DPV is a powerful technology to explore the valence band (VB) hole injection process of oxidized CIS/ZnS NCs or the CB electron injection process of reduced CIS/ZnS NCs under differed electrolyte conditions . According to Figure , CIS/ZnS NCs primarily exhibit two oxidative processes at around ∼0.4–0.5 and ∼0.8–1.0 V when the electrolyte is acidic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DPV is a powerful technology to explore the valence band (VB) hole injection process of oxidized CIS/ZnS NCs or the CB electron injection process of reduced CIS/ZnS NCs under differed electrolyte conditions . According to Figure , CIS/ZnS NCs primarily exhibit two oxidative processes at around ∼0.4–0.5 and ∼0.8–1.0 V when the electrolyte is acidic.…”
Section: Resultsmentioning
confidence: 99%
“…DPV is a powerful technology to explore the valence band (VB) hole injection process of oxidized CIS/ZnS NCs or the CB electron injection process of reduced CIS/ZnS NCs under differed electrolyte conditions. 34 According to Figure 3, CIS/ZnS NCs primarily exhibit two oxidative processes at around ∼0.4−0.5 and ∼0.8−1.0 V when the electrolyte is acidic. It was reported that CIS/ZnS NCs/N 2 H 4 • H 2 O system could also produce two ECL processes around 0.46 and 0.87 V under physiological conditions, which was consistent with the DPV results in this case.…”
Section: Characterizations Of Gsh/cit-capped Cis/zns Ncsmentioning
confidence: 99%
“…Thus, electron transfer reactions between emitters and the coreactants are critical to regulate the excitation efficiency and ECL trigger potential in coreactant-pathway ECL systems. 6−8 To date, various strategies have been developed to improve the above reactions, such as interparticle charge tansport, 8 electrocatalysis, 6,9 and intrareticular charge transfer-mediated competitive oxidation. 10 Nevertheless, most discussion was only at the phenomenological level, while a deeper intrinsic mechanism for ECL generation has yet to be elucidated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among them, electrochemiluminescence (ECL), a widely used light radiation energy output converted from electrochemical excitation, has evoked increasing interest for decades and becomes a powerful tool with precise temporal and spatial controllability, near-zero backgrounds, and a wide dynamic range. ECL relies on electron transfer reactions between the electrochemically generated highly reactive radical intermediates on an electrode surface. Thus, electron transfer reactions between emitters and the coreactants are critical to regulate the excitation efficiency and ECL trigger potential in coreactant-pathway ECL systems. To date, various strategies have been developed to improve the above reactions, such as interparticle charge tansport, electrocatalysis, , and intrareticular charge transfer-mediated competitive oxidation . Nevertheless, most discussion was only at the phenomenological level, while a deeper intrinsic mechanism for ECL generation has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, noble metal aerogels (NMAs) have attracted an extensive contribution of scientific projects because of their unbelieved morphology. These extraordinary NAs not only represent the 3D macrostructures with a very low density but also offer porous networks with abundant tunnels. Additionally, they reflect two unique characteristics for application in electrocatalysis-related processes: (1) The reactants can contact easily with the surface and inner active sites of NMAs because of their macroscopic character. (2) The durability relevant to a compound plays a pivotal role in commercializing catalysts.…”
Section: Introductionmentioning
confidence: 99%